1995
DOI: 10.1007/bf00290456
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a DNA sequence motif required for expression of iron-regulated genes in pseudomonads

Abstract: Many bacteria respond to a lack of iron in the environment by synthesizing siderophores, which act as iron-scavenging compounds. Fluorescent pseudomonads synthesize strain-specific but chemically related siderophores called pyoverdines or pseudobactins. We have investigated the mechanisms by which iron controls expression of genes involved in pyoverdine metabolism in Pseudomonas aeruginosa. Transcription of these genes is repressed by the presence of iron in the growth medium. Three promoters from these genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
74
3
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 48 publications
7
74
3
1
Order By: Relevance
“…Promoters that are recognized by RNA polymerase containing PvdS contain a sequence motif, the IS box, at about 33 bp from the transcription start sites and this forms part of the promoter sequence (Rombel et al, 1995;Wilson et al, 2001). A second sequence CGT at about 210 bp is also required for promoter recognition by PvdS (S. Tsao, M. J.…”
Section: Introductionmentioning
confidence: 99%
“…Promoters that are recognized by RNA polymerase containing PvdS contain a sequence motif, the IS box, at about 33 bp from the transcription start sites and this forms part of the promoter sequence (Rombel et al, 1995;Wilson et al, 2001). A second sequence CGT at about 210 bp is also required for promoter recognition by PvdS (S. Tsao, M. J.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription of pvdD could be terminated at either of these sites, giving a transcript of about 7.5 kb. The size of the transcript corresponding to pvdD was previously estimated to be 5 kb following Northern (RNA) analysis (36), but the sequence of the gene indicates that this is an underestimate, presumably due to the high degree of instability of this transcript (36).…”
mentioning
confidence: 99%
“…This protein is predicted to contain 803 amino (35) cloned into pUC9 (54) and contains DNA required for pyoverdine synthesis (34,35). Restriction fragments are labelled by using the same nomenclature as previously (36). The locations and orientations of two genes (pvdD and fpvA) sequenced in this study are shown.…”
mentioning
confidence: 99%
“…The sequences were analysed by standard methods with version 8.1-UNIX of the Computer Genetics Group package (Devereux et al, 1984) in conjunction with other programs as described previously ; sequence alignments were performed using  (Devereux et al, 1984) and residues were highlighted using BoxShade (http :\\ www.ch.embnet.org\software\BOXIform.html). Southern analysis was done by standard methods (Sambrook et al, 1989) with chromosomal DNA prepared by the method of Chen & Kuo (1993), and Northern (RNA) analysis was done as described previously (Rombel et al, 1995). Creating a mutation in pvdF.…”
Section: Methodsmentioning
confidence: 99%
“…2), that contains DNA required for synthesis of pyoverdine (Rombel & Lamont, 1992). Subsequent studies showed that this clone hybridized with five distinct ironregulated transcripts from P. aeruginosa (Rombel et al, 1995), with three of these corresponding to the pvdD, fpvA and pvdE genes (McMorran et al, 1996 ;Merriman et al, 1995 ;Poole et al, 1993). The first aim of this study was to characterize the gene corresponding to another of the iron-regulated transcripts.…”
Section: Sequence Analysismentioning
confidence: 99%